Resilience in public service partnerships: evidence from the UK Life Chances Fund - FitzGerald, C; Hameed, T; Rosenbach, F; Macdonald, JR; Dixon, R (Routledge, 2021)
This paper explores functional and structural resilience in outcomes-based public service partnerships. Using a theoretical framework informed by socio-ecological and health fields, and data from all thirty-one social impact bonds (SIBs) funded through the UK government’s Life Chances Fund, we explore how SIBs adapted service delivery and funding mechanisms in response to Covid-19. Human factors supported service continuity and adaptation, indicating the presence of functional resilience. Evidence of structural resilience was mixed, highlighting the importance of clear governance roles for determining structural changes during a crisis. Implications for an increasingly networked and partnership-based public service sector are discussed.